Structural Prediction of Bis{(di-p-anisole)1,4-azabutadiene}-bis[triphenylphosphine]ruthenium(II) Using 31P NMR Spectroscopy - Tay, Meng Guan; Ong, Kok Tong; Ruwaida Asyikin, Binti AbuTalip; Chia, Ying Ying; Thareni, Lokanathan (Hindawi Publishing Corporation, 2016)
The present paper reports the use of 31P NMR spectroscopy to predict the isomer structures of [bis{4-methoxy-phenyl-[3-(4methoxy-phenyl)-allylidene]-amino}]-bis[triphenylphosphine]ruthenium(II),also known as bis{(di-p-anisole)-1,4-azabutadiene}bis[triphenylphosphine]ruthenium(II),complexes.The complexation reaction was carried out under refluxing condition of (di-panisole)-1,4-azabutadiene(compound1), triphenylphosphine Ph3),and ruthenium chloride intheration of 2:2:1 for five hours. In addition, ruthenium(II) complexes were also characterized using FTIR and UV-Vis spectroscopy to support the formation of ruthenium(II)complexes. 31 PNMR spectroscopic study on ruthenium(II)complexes suggested that there are three is omers present after the complexation reaction and all the ruthenium complexes demonstrate octahedral geometry.